Some physical properties of two hard-setting calcium hydroxide bases - Lim, Albert S.; Cruz, Cynthia Bella L.; Macasaet, Avelino (Adviser).
The solubility in water and 37% phosphoric acid, and the compressive strength of two brands of hard-setting calcium hydroxide base materials were studied. One product differed significantly from the other with regard to acid solubility. There was no significant change or difference between the two products regarding water solubility and compressive strength.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Calcium Hydroxide